A new dual‐input high step‐up DC–DC converter with reduced switches stress and low input current ripple. Issue 9 (22nd May 2021) - Samadian, Ataollah; Hashemzadeh, Seyed Majid; Marangalu, Milad Ghavipanjeh; Maalandish, Mohammad; Hosseini, Seyed Hossein
Abstract: In this paper, a novel structure of non‐isolated dual‐input ultra‐high step‐up DC–DC converter with low voltage stress across semiconductor elements and low input current ripple is suggested. In the presented converter, when the power switches are turned‐OFF, two inputs inductors become series and the input current ripple will be reduced. This topology benefits from the superiorities of voltage multiplier cell and coupled inductor. The voltage conversion ratio can be controlled by coupled inductor turns ratio and duty cycle of power switches. So, the voltage conversion ratio of the suggested structure is flexible. Using the voltage multiplier cell not only increases the voltage gain, but also the voltage stress across power switches and diodes is decreased. In order to confirm the presented structure performance, the theoretical study includes operation principle and steady‐state analysis, and simulation results are provided. Also, the suggested converter has been compared with other similar converters versus voltage gain, efficiency, number of components, maximum voltage across switches and diodes. Finally, a 350 W experimental prototype of the converter is built to shows the effectiveness of the presented converter.